Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The problem given is this:

$\bigcap_{i \in I}(A_i \cup B_i)$ and $(\bigcap_{i \in I}A_i) \cup(\bigcap_{i \in I}B_i)$

I am asked if they are the same. Here is the reasoning I used:

for the first one: $\forall x(\forall i \in I(x \in A_i \vee x \in B_i))$

for the second one: $\forall x(\forall i \in I(x \in A_i) \vee \forall i \in I(x \in B_i))$

And using this for two families of sets:

$A_2 = \{2, 4\}, A_3 = \{3, 6\}$

$B_2 = \{2, 3\}, B_3 = \{3, 4\}$

I can't get the proper results which are:

$\bigcap_{i \in I}(A_i \cup B_i)$ = $\{3, 4\}$

$(\bigcap_{i \in I}A_i) \cup(\bigcap_{i \in I}B_i)$ = $\{3\}$

What I get is that they both contain all elements and are both equal, where am I going wrong with this?

share|improve this question
1  
Why do you think you're going wrong and where? The very first equality is false and you proved it with your example below! –  DonAntonio Feb 23 at 20:43
    
@DonAntonio the proper results are given to me next to the problem, I'm not actually reaching them on my own :( that's what I meant –  johan1234 Feb 23 at 20:44
    
Ok @johan, apparently you want to know why the outcome of the example. Read the answer. –  DonAntonio Feb 23 at 20:47
add comment

3 Answers

Let's see:

$$(A_2\cup B_2)\cap (A_3\cup B_3)=\{2,3,4\}\cap\{3,4,6\}=\{3,4\}$$

$$(A_2\cap A_3)\cup(B_2\cap B_3)=\emptyset\cup\{3\}=\{3\}$$

share|improve this answer
add comment

Like your counterexpample proves, the sets aren't the same. You only have this: $$\bigcap_{i\in I}(A_i\cup B_i)\supseteq\left(\bigcap_{i\in I} A_i\right)\cup\left(\bigcap_{i\in I}B_i\right)$$

But if $\left(\bigcup_{i\in I} A_i\right)\cap \left(\bigcup_{i\in I} B_i\right)=\emptyset$, then the other inclusion is also true.

This is because for every $x\in \bigcap_{i\in I}(A_i\cup B_i)$, $x$ is ether in every $A_i$ or every $B_i$.

share|improve this answer
add comment

Well as first you forgot the intersection You could reason it like this for the first set $\forall x((x \in A_1 \lor x \in B_1)\land (x \in A_2 \lor x \in B_2)\land\dots\land (x \in A_i \lor x \in B_i))$
For the second set $\forall x((x \in A_1 \land x \in A_2 \land \dots\land x\in A_i)\lor (x \in B_1 \land x \in B_2 \land \dots\land x\in B_i)\\ p_k=\tau(x \in A_k)\\q_k =\tau(x \in B_k)\\k \in I\\((p_1\lor q_1)\land(p_2\lor q_2)\land\dots\land(p_i\lor q_i))\iff (p_1\land p_2\land\dots\land p_i)\lor(q_1\land q_2\land\dots\land q_i)$ Transforming this to logic now it's pretty easy to prove that they're not the same,taking $p_1=\top \land q_2,q_3,\dots q_i=\top$ First one is true while the second one is false so it's not a tautology Not really sure is this is what you wanted.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.